Simple and rapid human papillomavirus genotyping method by restriction fragment length polymorphism analysis with two restriction enzymes. Issue 7 (22nd May 2013) - Chen, Linghan; Watanabe, Ken; Haruyama, Takahiro; Kobayashi, Nobuyuki
Abstract Cervical cancer, the third most common cancer that affects women worldwide, is caused by the human papillomavirus (HPV) and is treatable when detected at an early stage. To date, more than 100 different HPV types have been described, and the development of simple, low‐cost, and accurate methods to distinguish HPV genotypes is highly warranted. In this study, an HPV genotyping assay based on polymerase chain reaction (PCR) was evaluated. This method involved the use of MY09/11 primers followed by restriction fragment length polymorphism (RFLP) analysis with the restriction enzymes HpyCH4V and NlaIII. Cervical specimens preserved using CytoRich Blue fluid were collected from 1, 134 female volunteers for HPV detection, and 1, 111 valid samples were amplified using PCR. The PCR method was sensitive enough to detect 25 copies of HPV18, and three copies of HPV16. Out of 202 PCR‐positive samples, HPV genotypes were determined in 189 samples (93.6%) by this RFLP method. Results were then evaluated further by capillary sequencing method. Concordant results between the two tests were as high as 96.0%. Thirteen samples, which tested negative with RFLP, were verified as non‐specific amplifications with PCR. In conclusion, this PCR‐RFLP method using restriction enzymes HpyCH4V and NlaIII is simple, non‐labor intensive, and is applicable for the inexpensive determination of HPV genotypes in clinical samples. J. Med. Virol. 85:1229–1234, 2013. © 2013 Wiley Periodicals, Inc.